2015
DOI: 10.1159/000369010
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and Moderators of Change in Subjective Memory and Memory Performance: Findings from the Health and Retirement Study

Abstract: terns of associations emerged with respect to predictors of subjective memory and subjective memory change. First, the level of memory performance showed stronger associations with age, gender, and education, whereas subjective memory was more strongly associated with subjective age and personality traits. For example, women performed better than men on the episodic memory test, but there were no gender differences in subjective memory. Also, older age was associated with steeper declines of memory performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 40 publications
4
53
1
1
Order By: Relevance
“…The association of more Visit 1 self-SCC and fewer years of education, may align with the well-known protective effects (e.g., cognitive reserve; use of compensation strategies) of education on cognitive decline and rate of conversion to dementia (Karp et al, 2004; Letenneur et al, 2000; Qiu, Bäckman, Winblad, Agüero-Torres, & Fratiglioni, 2001; Stern et al, 1994; van Oijen, de Jong, Hofman, Koudstaal, & Breteler, 2007). However, studies have observed steeper rates of decline in self-SCC (more complaints) in more highly educated individuals (Hulur, Hertzog, Pearman, Ram, & Gerstorf, 2014; Hulur et al, 2015; Zelinski, Burnight, & Lane, 2001); and when self-SCC complaints are present, appear to be more predictive of cognitive decline and AD risk compared to that in less educated individuals (Chary et al, 2013; van Oijen et al, 2007. Thus, there may be a period of delay of self-reported cognitive changes in at-risk individuals who are highly educated, and then eventually convert at a faster rate later in time after accumulation of neurodegenerative processes (Stern, Albert, Tang, & Tsai, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of more Visit 1 self-SCC and fewer years of education, may align with the well-known protective effects (e.g., cognitive reserve; use of compensation strategies) of education on cognitive decline and rate of conversion to dementia (Karp et al, 2004; Letenneur et al, 2000; Qiu, Bäckman, Winblad, Agüero-Torres, & Fratiglioni, 2001; Stern et al, 1994; van Oijen, de Jong, Hofman, Koudstaal, & Breteler, 2007). However, studies have observed steeper rates of decline in self-SCC (more complaints) in more highly educated individuals (Hulur, Hertzog, Pearman, Ram, & Gerstorf, 2014; Hulur et al, 2015; Zelinski, Burnight, & Lane, 2001); and when self-SCC complaints are present, appear to be more predictive of cognitive decline and AD risk compared to that in less educated individuals (Chary et al, 2013; van Oijen et al, 2007. Thus, there may be a period of delay of self-reported cognitive changes in at-risk individuals who are highly educated, and then eventually convert at a faster rate later in time after accumulation of neurodegenerative processes (Stern, Albert, Tang, & Tsai, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies using multiple time points and controlling for known confounding factors (e.g., depressive symptoms), have generally found a modest relationship between SCC and OM (Crumley, Stetler, & Horhota, 2014; Hulur, Hertzog, Pearman, & Gerstorf, 2015; Mascherek & Zimprich, 2011; Parisi et al, 2011) although some have not (Pearman, Hertzog, & Gerstorf, 2014). Differences in methodology and sample characteristics may in part account for these discrepancies.…”
Section: Introductionmentioning
confidence: 99%
“…Some complaints may arise from concerns about aging among the “worried well” given that memory complaints are often more strongly correlated with depression or neuroticism than they are with memory test performance [for recent reviews, see 22, 23]. Adults’ performance on memory tasks correlates with subjective memory, both cross-sectionally and longitudinally, independent of the relationship to depressive and anxious affect [e.g., 21, 24]. However, the magnitude of the relationship of subjective memory beliefs to memory performance is often rather low.…”
Section: Introductionmentioning
confidence: 99%
“…osobnostné vlastnosti, pohlavie, vzdelanie, stratégia učenia, orientácia na cieľ atď. (Carr, Castel, & Knowlton, 2015;Hülür, Hertzog, Pearman, & Gerstorf, 2015, Lee, Ning, & Goh, 2014. Kormi-Nouri et al (2008) poukázali na lepšiu sémantickú i epizodickú pamäť bilingválnych v porovnaní s monolingválnymi, pričom táto výhoda sa ukázala v oboch jazykoch dvojjazyčných.…”
Section: Diskusiaunclassified